how would i write this in standard form and get the circle and radius and graph it? i've been on several sites reading and watching tutorials.
-
You need to complete the square for both variables x and y.
x² + y² - 2x - 6y + 6 = 0
(x² - 2x) + (y² - 6y) = -6
(x² - 2x + __) + (y² - 6y + __) = -6 + __ + __
To complete first square (in x) we add 1
To complete second square (in y) we add 9
(x² - 2x + 1) + (y² - 6y + 9) = -6 + 1 + 9
(x - 1)² + (y - 3)² = 4
Centre: (1, 3)
Radius: 2
Mαthmφm
x² + y² - 2x - 6y + 6 = 0
(x² - 2x) + (y² - 6y) = -6
(x² - 2x + __) + (y² - 6y + __) = -6 + __ + __
To complete first square (in x) we add 1
To complete second square (in y) we add 9
(x² - 2x + 1) + (y² - 6y + 9) = -6 + 1 + 9
(x - 1)² + (y - 3)² = 4
Centre: (1, 3)
Radius: 2
Mαthmφm
-
(x² - 2x) + (y² - 6y) = - 6
(x² - 2x + 4) + (y² - 6y + 9) = - 6 + 4 + 9
(x - 2)² + (y - 3)² = 7 = r²
Equation of circle centre (2 , 3) and radius √7
(x² - 2x + 4) + (y² - 6y + 9) = - 6 + 4 + 9
(x - 2)² + (y - 3)² = 7 = r²
Equation of circle centre (2 , 3) and radius √7
-
x^2+y^2-2x-6y=-6+1+9
(x-1)^2 + (y-3)^2 =4
square root of 4=2
radius=2
(x-1)^2 + (y-3)^2 =4
square root of 4=2
radius=2